2009
DOI: 10.1007/s10639-009-9112-1
|View full text |Cite
|
Sign up to set email alerts
|

Preservice teachers’ perspectives on the definition and assessment of creativity and the role of web design in developing creative potential

Abstract: This empirical study explores the perspectives of eight preservice teachers on the meaning and assessment of creativity and the role of web design in developing creative potential. Data sources included eight semi-structured interviews analyzed by three independent raters, web design checklists, and interviewer's notes. Five themes emerged from participant responses during data analysis: a) definition of creativity, b) assessment of creativity, c) creativity and instructional strategies, d) creativity and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…Through a survey of 285 pre‐service music and visual arts teachers in Hong Kong that examined creativity and assessment in arts education, Leong and Qiu () found that respondents indicated a far greater understanding of how to support and assess skill development over creativity, and a belief that they should focus their teaching on tests and exams rather than on assessment practices that foster creativity. In the US, eight pre‐service teachers were asked about their perceptions of creativity by Antonenko and Thompson () and described creativity as a broad concept that could not be pinned down or reduced to a list of adjectives. These future teachers indicated a general preference for a ‘subjective’, holistic assessment of creativity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Through a survey of 285 pre‐service music and visual arts teachers in Hong Kong that examined creativity and assessment in arts education, Leong and Qiu () found that respondents indicated a far greater understanding of how to support and assess skill development over creativity, and a belief that they should focus their teaching on tests and exams rather than on assessment practices that foster creativity. In the US, eight pre‐service teachers were asked about their perceptions of creativity by Antonenko and Thompson () and described creativity as a broad concept that could not be pinned down or reduced to a list of adjectives. These future teachers indicated a general preference for a ‘subjective’, holistic assessment of creativity.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to identify any meaningful pattern amongst the findings in this section, other than the indication that teachers’ orientations to the teaching and assessment of creativity are highly variable. While some studies indicated that teachers’ limited, broad, or vague conceptions of creativity were accompanied by avoiding creativity assessment (Myhill & Wilson, ; Leong & Qui, ; Gardiner, ), or resorting to holistic assessment (Antonenko & Thompson, ), other studies indicated that some teachers did value assessing creativity, and were making efforts to do so (e.g., visual arts teachers in Hong Kong, Leong, ; drama teachers in Canada, Jamaica, the US and Norway, McCammon et al, ; and music teachers in Slovenia, Rozman, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…suggests that people learn best by building (Papert and Harel, 1991;Alimisis et al, 2009;Klopfer et al, 2009a;Antonenko and Thompson, 2011). Asking the students to design their own experiment with the simulation provides an enquiry-based educational experience (HmeloSilver et al, 2007;Deigan, 2009), increasing student perception of "ownership" of their work (Palmer, 2002).…”
Section: Special Editionmentioning
confidence: 99%